OP0265 Local reactivation of glucocorticoids by 11Β-hydroxysteroid dehydrogenase type 1 mediates the development of glucocorticoid-induced bone loss. (12th June 2018) - Fenton, C; Doig, C.; Fareed, S.; Naylor, A.; Wehmeyer, C.; Buckley, C.; Lavery, G.; Cooper, M.; Raza, K.; Hardy, R.
Abstract : Background: Due to the potent immunomodulatory and anti-inflammatory nature of glucocorticoids (GCs) they are routinely used in the treatment of inflammatory diseases such as rheumatoid arthritis. However their therapeutic potential is limited due to the prevalence of adverse side effects associated with long term GC exposure such as osteoporosis, insulin resistance and obesity. 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is a bi-directional enzyme that primarily converts inactive GCs to their active counterparts. Previously, local reactivation of GCs by 11β-HSD1 has been shown to play a major role in the metabolic side effects associated with GC excess. Objectives: We aim to assess whether local reactivation of GCs by 11β-HSD1 mediates the adverse effects of therapeutic GCs on bone. Methods: Wild-type (WT) mice and transgenic mice with a global 11β-HSD1 knockout (11βKO) were treated with the active murine GC corticosterone (CORT) (100 mg/ml) for 4 weeks. Tibia and humerus bones were excised post-mortem for micro-CT analysis, gene expression analysis and three point flexure strength (TFS) tests. Serum was collected from mice for ELISA analysis of TRAcP-5b and P1NP. Results: Micro-CT analysis of bone volume to tissue volume (BV/TV), trabecular thickness (TT) and trabecular number (TN) found no significant differences between untreated WT and 11βKO mice (BV/TV: WT 8.5%±0.66 vs 11βKO 7.5%±0.76, NS; TT: WT 96.5 µm±3.8 vs 11βKO 95.8 µm±6.4, NS; TN: WT 0.0009 1/µm±0.00004 vs 11βKO 0.0008 1/μm±0.00004, NS). Humerus TFS tests of WT and 11βKO animals also showed no significant differences (WT 51.2 MPa±15.1 vs 11βKO 49.2 MPa±4.9, NS). All bone parameters were decreased in CORT fed WT mice indicating the development of osteoporosis, whilst 11βKO mice were protected against many of the detrimental effects of CORT (BV/TV: WT 4.2%±0.38 vs 11βKO 7.2%±0.71, p≤0.05; TN: WT 0.0006 1/µm±0.00004 vs 11βKO 0.0009 1/µm±0.00008, p≤0.001; HBS: WT 27.1 MPa±5.6 vs 11βKO±50 MPa±5.1, p≤0.05). ELISA analysis of mouse serum showed no significant differences in the bone resorbing osteoclast marker TRAcP-5b amongst the groups, whereas analysis of the bone forming osteoblast marker P1NP revealed a significant increase in CORT fed 11βKO mice compared with CORT fed WT mice (11βKO 158.6 ng/ml±53.1 vs WT 31.4 ng/ml±7.4, p≤0.05). Gene expression of the mature osteoblast markers ALP (alkaline phosphatase) and BGLAP (osteocalcin) showed significant increases in CORT fed 11βKO animals compared to CORT fed WT animals (ALP: 11βKO 0.0074 AU ±0.0012 vs WT 0.0022 AU ±0.0007, p≤0.01; BGLAP: 11βKO 0.27 AU ±0.04 vs WT 0.02 AU ±0.01, p≤0.001). No significant differences were observed between untreated WT and 11βKO animals. Conclusions: These data suggest that local reactivation of GCs by 11β-HSD1 mediates the development of glucocorticoid-induced osteoporosis by inhibiting osteoblastic bone formation. Reference: [1] Morgan SA, McCabe EL, Gathercole LL, Hassan-Smith ZK, Larner DP, Bujalska IJ, et al. 11beta-HSD1 is the major regulator of the tissue-specific effects of circulating glucocorticoid excess. Proceedings of the National Academy of Sciences of the United States of America2014;111(24):E2482–91. Disclosure of Interest: None declared